1973
DOI: 10.1002/j.1551-8833.1973.tb01793.x
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Method for Determining Organics by Activated Carbon Adsorption and Solvent Extraction—Part I

Abstract: Increasingly, organics in water are receiving attention. According to the authors of this article, there has been no apparatus that combines the features of low cost, reliability, portability, and ease of use until now.Here is a first installment, detailing the apparatus and describing, gen erally, the ramifications of testing. In March, the JOURNAL will publish complete test procedures.*Because the concentration of CCE may vary, depending upon the method of collection and extraction, additional lower-case let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1973
1973
1977
1977

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Sorbents from CROCA samplers were washed with an acidic solution of hydroxylamine hydrochloride to remove iron hydroxide that prevented the efficient elution of the sorbents. Studies have shown that the Phenols (10) Chlorinated alkanes and alkenes (5) Chlorinated aromatic compounds (13) Aromatic compounds (7) Aldehydes and ketones (3) Amines (13) Carboxylic Acids (11] Pesticides ( present at levels > 0.01 /ig/1 in water sample fTotal concentration of all gas chromatographable material in ex racts in |ig/l. based on GC detector sensitivity for tetradecane JAmount of organic material n extract of primary sorption co umn divided by amount in extracts of primary and secondary sorption beds **Average, excluding two highest and two lowest municipalities and the two coal related sources of water k acidic-reductant wash does not produce a detectable change in the number or intensity of gas chromatographable compounds eluted from either carbon or resin.…”
Section: Resultsmentioning
confidence: 99%
“…Sorbents from CROCA samplers were washed with an acidic solution of hydroxylamine hydrochloride to remove iron hydroxide that prevented the efficient elution of the sorbents. Studies have shown that the Phenols (10) Chlorinated alkanes and alkenes (5) Chlorinated aromatic compounds (13) Aromatic compounds (7) Aldehydes and ketones (3) Amines (13) Carboxylic Acids (11] Pesticides ( present at levels > 0.01 /ig/1 in water sample fTotal concentration of all gas chromatographable material in ex racts in |ig/l. based on GC detector sensitivity for tetradecane JAmount of organic material n extract of primary sorption co umn divided by amount in extracts of primary and secondary sorption beds **Average, excluding two highest and two lowest municipalities and the two coal related sources of water k acidic-reductant wash does not produce a detectable change in the number or intensity of gas chromatographable compounds eluted from either carbon or resin.…”
Section: Resultsmentioning
confidence: 99%
“…Recovery with the new miniature technique for the CCE is about seven times as great as with the older techniques and for the CAE is about twenty times the previous. 21 The proposed standards will contain "health" limits of 0.7 mg/1 for CCEm and 3.0 mg/1 for CAEm. A redetermination should be made as to the proper goals when functioning with the miniature technique.…”
Section: Copper (Cu)mentioning
confidence: 99%
“…Clean ground waters are reported to show about 0.1 mg/1 of CCEm and about 0.3-0.4 mg/1 of CAEm. 21 The ability of activated carbon to reduce the organic content of water has been repeatedly proved in practical water treatment. Hynshaw22 has recently shown that carbon will readily reduce the content of some of the common insecticides (Parathion, BHC, Malathion, and DDT) from TON of 50 or more to acceptable odor levels utilizing moderate dosages of carbon.…”
Section: Copper (Cu)mentioning
confidence: 99%
“…These concentrations are about three times CCE-lf data on the same water 3. be avoided because it shortens the effective length of the sample column, thereby reducing the space for the 70.0 g of activated carbon and restricting the cleansing of the activated carbon during flushing.Start of sampling.…”
mentioning
confidence: 99%